Photonic Crystals and Light Localization in the 21st Century 2001
DOI: 10.1007/978-94-010-0738-2_34
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of localization in a waveguide

Abstract: Abstract. This is a review of the dynamics of wave propagation through a disordered JV-mode waveguide in the localized regime. The basic quantities considered are the Wigner-Smith and single-mode delay times, plus the time-dependent power spectrum of a reflected pulse. The long-time dynamics is dominated by resonant transmission over length scales much larger than the localization length. The corresponding distribution of the Wigner-Smith delay times is the Laguerre ensemble of random-matrix theory. In the pow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…(A.3) 28 The relation between the dynamical problem (real ω) and the static problem with absorption (complex ω) was used in another context in Refs. [116,168,14,17,84]. leading to (187).…”
Section: T T a Tmentioning
confidence: 99%
See 1 more Smart Citation
“…(A.3) 28 The relation between the dynamical problem (real ω) and the static problem with absorption (complex ω) was used in another context in Refs. [116,168,14,17,84]. leading to (187).…”
Section: T T a Tmentioning
confidence: 99%
“…The most fundamental aspects of time delays have been reviewed by Carvalho and Nussenzveig [67]. Some other articles have reviewed more specific aspects : Beenakker has considered the case of wave guides in the localised regime [14]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The set {τ n } of eigenvalues of the Wigner-Smith matrix Q, the so-called proper time delays, provide a set of characteristic times of the scattering problem. Their joint distribution was obtained by Brouwer and Beenakker (assuming a semi-infinite disordered region) [6,7], who showed that Q −1 belongs to the Laguerre ensemble : in appropriate units, the joint probability density for the rates λ i = 1/τ i is…”
Section: Wigner-smith Matrix and Wigner Time Delaymentioning
confidence: 99%
“…Therefore, with the knowledge of � L (n; α) and the delay-time probability density for canonical disordered systems, p s (τ R ) , we write the probability density p α (τ R ) for Lévy disordered systems as The probability density p s (τ R ) in its full generality remains, however, an open problem. For semi-infinite disordered systems, assuming no transmission, the limit ( L → ∞ ) delay-time distribution p ∞ (τ R ) is given by 11,[41][42][43][44][45] :…”
Section: Resultsmentioning
confidence: 99%
“…where τ 0 is the absorption time which is assumed very large [45][46][47] . A key point is that this relationship establishes that fluctuations of R determine the statistics of τ R .…”
Section: Resultsmentioning
confidence: 99%